Proposal for knowledge capturing tool for Malaysian herbs researchers - Azlida Mamat, 1982-, author; Azizah Abdul Rahman, author; Mazenah Youp, author; Postgraduate Annual Research Seminar (4th : 2008 : Johor) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL